Comparação dos parâmetros cinéticos da xantina desidrogenase em neoplasia experimental - Affonso, Ottilia R. (2023)
The behaviour of xanthine dehydrogenase (XD) was examined in normal serum and in the sérum of rats with sarcoma. XD decreased in the serum of tumour bearing host. The affinity of XD to xanthine was similar in normal serum and in serum of tumour bearing rats. Inactivation at 70°C is apparently first order with respect to enzyme concentration. XD activity was linear during 60 min incubation and the tumour sérum enzyme was more sensitive to different inhibitors. We conclude that there are not substantial differences in the structures in both XD and it is assumed that the decreased XD activity in the sarcoma neoplasms indicated Iowered enzyme concentration.